K.H. Muhammad Nuh and the Role of Islamic Cultural Development in Cilongok 1900-1986 (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2025)
K.H. Muhammad Nuh played a role in the development of Islamic culture in Cilongok from 1900-1986. The purpose of this research is to determine the development and role of K.H. Muhammad Nuh towards Islamic culture in Cilongok. The research method used is local history. In this research, researchers used research steps with several stages including: Heuristics, Verification, Interpretation, and Historiography. The results of this research show that after the arrival of K.H. Muhammad Nuh came to Cilongok in 1936 and had an influence on the development of Islamic culture. The arrival of K.H. Muhammad Nuh played a significant role in the increasingly widespread development of Islamic culture. Through the da'wah spread by K.H. Muhammad Nuh had a good influence on the surrounding community and even built an Islamic educational institution which was attended by the surrounding community and two students who were followers of K.H. Muhammad Nuh. After that, every month of Ramadhan many students came from other areas until it became the Darul Hikmah Islamic Boarding School until now. The conclusion in this research is that K.H. Muhammad Nuh played a strong role in developing Islamic culture in Cilongok.